Polymeric Nanoscale Drug Carriers Mediate the Delivery of Methotrexate for Developing Therapeutic Interventions Against Cancer and Rheumatoid Arthritis - Yu, Wen-Jun; Huang, Dong-Xu; Liu, Shuang; Sha, Ying-Li; Gao, Feng-hui; Liu, Hong (Frontiers in Oncology, 2020)
Methotrexate (MTX) is widely used as an anticancer and anti-inflammtory drug for treating various types of cancer and autoimmune diseases. The optimal dose of MTX is known to inhibit the dihydrofolate reductase (DHFR) that hinders the replication of purines. The nanobiomedicine has been extensively explored in the past decade to develop a myriad of functional nanostructures to facilitate the delivery of therapeutic agents for various medical applications. This review is focused to understanding the design & development of MTX loaded nanoparticles alongside the inclusion of recent findings for the treatment of cancers. In this paper, we have put coordinated efforts to show the potential of novel drug delivery systems (NDDS) by achieving the effective and target-specific delivery of methotrexate.